KANDUNGAN PROTEIN KASAR DAN SERAT KASAR TONGKOL JAGUNG YANG DIFERMENTASI DENGAN MENGGUNAKAN TINGKAT CAIRAN RUMEN KERBAU YANG BERBEDA - Neni Widaningsih; Siti Dharmawati; Novi Puspitasari (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This study based on analyzing the crude protein and crude fibre on the fermented corn cobs using deferent level of buffalo rumen fluid. Research compiled based on experiment with Complete Random Design (CRD) with 5 treatments and 4 replications namely T0 = 0% buffalo rumen fluid (control), T1 = 20% buffalo rumen fluid, T2 = 40% buffalo rumen fluid, T3 = 60% buffalo rumen fluid, T4 = 80% buffalo rumen fluid. The variables measured is the value of crude protein and crude fiber. Result of this research show that using buffalo rumen fluid at 80% level could be increase the highest crude protein (28,38%) and decrease the lowest crude fibre (8.22%). Concluded that the buffalo rumen fluid could be turn up crude protein and turn down crude fiber of corn cob fermentation. Advised many buffalo rumen fluid that can be administered to a corn cob fermentation is as much as 80%.